'Annexins' themed section. (April 2015) - Flower, R J; Perretti, M
Abstract : Linked Articles: This article is part of a themed section on Annexins VII Programme. To view the other articles in this section visithttp://dx.doi.org/10.1111/bph.2015.172.issue‐7